2018
DOI: 10.1093/jn/nxx034
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Requirements of Healthy Pregnant Women are Higher During Late Stages of Gestation Compared to Early Gestation

Abstract: Background: Lysine is the first limiting amino acid in cereal proteins and is found mainly in animal-derived products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
3
19
0
1
Order By: Relevance
“…Lastly, a recent study on healthy pregnant women in Canada reported that the protein requirement could be higher than the current DRI recommendation [ 39 ]. The same research group subsequently showed increased requirements of specific indispensable amino acids, such as lysine and phenylalanine, during pregnancy [ 40 , 41 ]. Thus, caution may be necessary to view the risk of FGR and LBW in the context of maternal protein intake.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a recent study on healthy pregnant women in Canada reported that the protein requirement could be higher than the current DRI recommendation [ 39 ]. The same research group subsequently showed increased requirements of specific indispensable amino acids, such as lysine and phenylalanine, during pregnancy [ 40 , 41 ]. Thus, caution may be necessary to view the risk of FGR and LBW in the context of maternal protein intake.…”
Section: Discussionmentioning
confidence: 99%
“…To separate a potential confounding factor of prior familiarity of QPP and its nutritional characteristics compared to commercialized varieties, the taste test was held at Colby Community College in Colby, Kansas and participants were asked to rate six popcorn varieties based solely on sensory factors without prior knowledge of QPP's higher levels of essential amino acids lysine and tryptophan in the popped flake compared to commercialized varieties (Parsons et al, 2020). This specific increase in these two deficient amino acids in maize allows QPP to be considered a complete protein source, a “Functional Food”, or a food with an inclusion of certain substances with proven health benefits, and a “superfood”, or a relatively more nutrient dense and healthy product (Curll, Parker, MacGregor, & Petersen, 2016; Ghosh et al, 2008, 2010; MacGregor, Petersen, & Parker, 2018; Meyerding, Kürzdörfer, & Gassler, 2018; Murphy, Longhitano, Ayres, Cowen, & Harmer, 2006; Payne et al, 2018; Ritze, Bárdos, Hubert, & Bischoff, 2013; Tahergorabi, Matak, & Jaczynski, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Protein requirements are increased from early pregnancy and increase throughout gestation [ 8 , 19 ]. Contemporary methods such as in vivo amino acid oxidation suggest previous estimates of gestational protein requirements, based historically from extrapolation of nitrogen balance studies in men, may be insufficient, especially in late pregnancy, Fig.…”
Section: Biological Adaptations To Pregnancymentioning
confidence: 99%